2006
DOI: 10.1182/blood-2005-05-1896
|View full text |Cite
|
Sign up to set email alerts
|

SHPS-1 promotes the survival of circulating erythrocytes through inhibition of phagocytosis by splenic macrophages

Abstract: IntroductionThe lifespan of circulating red blood cells (RBCs) is approximately 120 and 40 days in humans and mice, respectively, and is determined by their production in bone marrow (BM) and their clearance from the peripheral circulation, predominantly in the spleen and liver. [1][2][3] The production of RBCs is controlled by the primary erythropoietic regulator erythropoietin, 2,4 whereas clearance of old RBCs by the spleen is achieved mostly as a result of their specific recognition and phagocytosis by spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 45 publications
7
115
0
Order By: Relevance
“…Resolution of at least two puzzles remains paramount: first, why macrophages do not attack self in mice deficient of Cd47 or Sirpα? Despite that the Cd47-Sirpα-mediated inhibition is missing, mice deficient of Cd47 (26), Sirpα (established in this study), or the Sirpα cytoplasmic domain (27) are relatively healthy, manifesting no or only minor phenotypes (9,18,28) that suggest macrophage phagocytosis toward self-cells. Adoptive transfer of Cd47-null RBCs into these mutant mice also failed to induce rapid elimination (1) (also shown in this study).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Resolution of at least two puzzles remains paramount: first, why macrophages do not attack self in mice deficient of Cd47 or Sirpα? Despite that the Cd47-Sirpα-mediated inhibition is missing, mice deficient of Cd47 (26), Sirpα (established in this study), or the Sirpα cytoplasmic domain (27) are relatively healthy, manifesting no or only minor phenotypes (9,18,28) that suggest macrophage phagocytosis toward self-cells. Adoptive transfer of Cd47-null RBCs into these mutant mice also failed to induce rapid elimination (1) (also shown in this study).…”
Section: Significancementioning
confidence: 99%
“…conjunction with therapeutic anticancer antibodies (4,9,(16)(17)(18)(19)(20)(21). Conversely, the lack of a compatible CD47 to ligate the recipient SIRPα is considered to be associated with tissue rejection in xenotransplantation (22)(23)(24)(25).…”
Section: Significancementioning
confidence: 99%
“…Furthermore, the phagocytosis of CD47-deficient RBCs by either splenic or bone marrow-derived macrophages was markedly enhanced in an in vitro assay (6,7). Conversely, we recently showed that the rate of clearance of transfused RBCs from the bloodstream was markedly increased in mice that express a mutant SHPS-1 protein lacking most of the cytoplasmic region, compared with that apparent for WT mice (9). In addition, phagocytosis of opsonized RBCs by peritoneal macrophages (PEMs) derived from the SHPS-1 mutant mice was enhanced compared with that apparent with WT PEMs (8).…”
mentioning
confidence: 96%
“…The surface expression of SHPS-1 on RAW264.7 cells was examined by flow cytometry, as described (8,9). In brief, cells were detached from culture dishes by treatment with 0.01% EDTA and then washed with icecold PBS.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation